The Effect of Financial Behavior on Financial Performance of Transportation Companies in Indonesia - Candra, Alex; Yuniarwati (Research Horizon, 2025)
This study aims to analyze the influence of financial behavior on financial performance, the influence of financial distress on financial performance, and the moderating role of financial distress in the relationship between financial behavior and financial performance of transportation companies in Indonesia. The study employed a quantitative approach with a descriptive-verifiable design. The population consisted of mid-sized transportation companies in Greater Jakarta (Jabodetabek), with 105 valid questionnaires collected from financial managers and heads of relevant divisions. The study variables, measured using a 5-point Likert scale questionnaire. Data analysis was conducted using PLS-SEM with SmartPLS. The results showed that financial behavior had a significant positive effect on financial performance, while financial distress had a significant negative effect. Furthermore, financial distress moderated the relationship between financial behavior and financial performance, suggesting that financial stress can reduce the effectiveness of sound financial practices. These findings underscore the importance of a comprehensive financial management strategy, including improving financial literacy, risk management, and sound financial planning, to maintain company performance under normal conditions and financial stress.